Dynamics responses of railway bridges influenced by flooded ballasted tracks subjected to high-speed trains - Naveen Kumar Kedia; Ratabhat Wangtawesap; Chayut Ngamkhanong (Transportation Engineering)
This study focuses on the dynamics of the train-track-bridge interaction system, specifically addressing the challenges posed by saturated ballasted tracks due to insufficient drainage during extreme flooding events. A full-scale sleeper-ballast experiment is first conducted using instrumented impact hammer excitation and a minimization algorithm, which characterizes the dynamic behaviour of sleeper-ballast interaction at varying water levels (0–35 cm). The ballast stiffness and damping are condensed into a single parameter using the Guyan condensation scheme, revealing increased damping and reduced stiffness with rising water levels. The condensed parameters are then used in the two-dimensional Train-Track-Bridge-Dynamic-Interaction-Systems (TTBDIS), which are validated with published literature to carry out the parametric studies. The dynamic response of the interaction system is influenced by a complex interplay of factors, including the inverse relationship between track stiffness and damping, an aspect that has not been previously investigated. Findings indicate that lower water levels are critical for dynamic amplification on longer-span bridges, while higher water levels are critical for shorter spans. Critical speeds emerge when the bridge’s fundamental frequency aligns with higher harmonics of dominant and driving frequencies, causing dynamic responses that exceed safety limits. The general dominance weight analysis further revealed that the bridge’s mass is the most significant factor, followed by track damping, span length, track stiffness, and train speed. The findings are crucial to understanding the behaviour of railway bridges during extreme flooding, helping railway authorities mitigate their adverse impacts, making them more climate resilient, and improving design and maintenance regimes.